умоляю помогите
Раскройте скобки и упростите выражение:
№1.
а) 2x – (2x + y) + y =
б) – a + (2a – b) + 2b =
в) 7 – (b + 14) – 2b =
г) 3b – (18 + b) + 8 =
№2.
а) 2(3 – x) – (8 + x) =
б) – 4(y + 5) + (12 – y) =
в) – (7 – x) + 4(x – 5) =
г) – 9(y – 4) – (12 + y) =
№3. Решите уравнение:
а) 3x – 5x = -−13 +3
б) – 5y –17y = -−50 +6
в) a –12a = -−6 − 27
г) –27x –33x = –12 ∙ (−-5)
№4. Раскройте скобки и упростите выражения:
–12(7 −2d) –9(7d –5) –3(15 +8d) =

Answer :

ItzBlueish

ответы:

№1

а) [tex]0[/tex]

б) [tex]a+b[/tex]

в) [tex]-3b-7[/tex]

г) [tex]2b-10[/tex]

№2

а) [tex]-3x-2[/tex]

б) [tex]-5y-8[/tex]

в) [tex]5x-27[/tex]

г) [tex]-10y+24[/tex]

№3

а) [tex]x=5[/tex]

б) [tex]y=2[/tex]

в) [tex]a=3[/tex]

г) [tex]x=-1[/tex]

№4

[tex]-63d-84[/tex]

Пошаговое объяснение:

[tex]2x-(2x + y) + y[/tex]

[tex]=2x-2x-y+y[/tex]

[tex]=0[/tex]

[tex]-\:a\:+\:\left(2a\:-\:b\right)\:+\:2b\:[/tex]

[tex]=-a+2a-b+2b[/tex]

[tex]=a-b+2b[/tex]

[tex]=a+b[/tex]

[tex]7-\left(b+14\right)-2b[/tex]

[tex]=7-b-14-2b[/tex]

[tex]=-3b-7[/tex]

[tex]3b-\left(18+b\right)+8[/tex]

[tex]=3b-18-b+8[/tex]

[tex]=2b-10[/tex]

[tex]2\left(3-x\right)-\left(8+x\right)[/tex]

[tex]=6-2x-\left(8+x\right)[/tex]

[tex]=6-2x-8-x[/tex]

[tex]=-3x-2[/tex]

[tex]-4\left(y+5\right)+\left(12-y\right)[/tex]

[tex]=-4\left(y+5\right)+12-y[/tex]

[tex]=-4y-20+12-y[/tex]

[tex]=-5y-8[/tex]

[tex]-\left(7-x\right)+4\left(x-5\right)[/tex]

[tex]=-7+x+4\left(x-5\right)[/tex]

[tex]=-7+x+4x-20[/tex]

[tex]=5x-27[/tex]

[tex]-9\left(y-4\right)-\left(12+y\right)[/tex]

[tex]=-9y+36-\left(12+y\right)[/tex]

[tex]=-9y+36-12-y[/tex]

[tex]=-10y+24[/tex]

[tex]3x-5x=-13+3[/tex]

[tex]-2x=-13+3[/tex]

[tex]-2x=-10[/tex]

[tex]\frac{-2x}{-2}=\frac{-10}{-2}[/tex]

[tex]x=5[/tex]

[tex]-5y-17y=-50+6[/tex]

[tex]-22y=-50+6[/tex]

[tex]-22y=-44[/tex]

[tex]\frac{-22y}{-22}=\frac{-44}{-22}[/tex]

[tex]y=2[/tex]

[tex]a-12a=-6-27[/tex]

[tex]-11a=-6-27[/tex]

[tex]-11a=-33[/tex]

[tex]\frac{-11a}{-11}=\frac{-33}{-11}[/tex]

[tex]a=3[/tex]

[tex]-27x-33x=-12\left(-5\right)[/tex]

[tex]-60x=-12\left(-5\right)[/tex]

[tex]-60x=12\cdot \:5[/tex]

[tex]-60x=60[/tex]

[tex]\frac{-60x}{-60}=\frac{60}{-60}[/tex]

[tex]x=-1[/tex]

[tex]-12\left(7-2d\right)-9\left(7d-5\right)-3\left(15+8d\right)[/tex]

[tex]=-84+24d-9\left(7d-5\right)-3\left(15+8d\right)[/tex]

[tex]=-84+24d-63d+45-3\left(15+8d\right)[/tex]

[tex]=-84+24d-63d+45-45-24d[/tex]

[tex]=24d-63d-24d-84+45-45[/tex]

[tex]=-63d-84+45-45[/tex]

[tex]=-63d-84[/tex]

Other Questions